DESIGNING AN ESP COURSE FOR MIDWIFERY STUDENTS IN STIKES PRIMA JAMBI - Silvia, Resi (SCIENTIA JOURNAL, 2016)
Designing teaching material is the process of selecting, adapting and evaluating of teaching based onspecific terms of reference. Need Analysis is very important before designing teaching materials forEnglish for Specific Purpose. Much attention should be drawn to the design of ESP courses whichcan help to prepare learners for future professional in workplaces. The study aims at exploring thelearning needs of 36 midwifery students in STIKes Prima Jambi, and designing ESP materials formidwife based on Need Analysis. When designing an ESP course, the primary issue is the analysis oflearners’ specific needs. Other issues addressed include: determination of realistic goals andobjectives; integration of grammatical functions and acquisition skills; and assessment and evaluation.Although ESP contexts view these issues from their own perspectives, the proposed framework forESP course development is argued as being of benefit to teachers who may encounter problems inESP course design.